Pengaruh pemberian Cognitive Behavior Therapy (CBT) terhadap penurunan kecemasan berbicara pada mahasiswa psikologi - Firmansyah, Aris Dimas (Maliki Interdisciplinary Journal, 2024)
This study aims to determine the effect of giving Cognitive Behavior Therapy (CBT) to reduce the level of anxiety of public speaking in psychology students at the State Islamic University of Maulana Malik Ibrahim Malang. The method used in this study was a quantitative experiment, namely giving pre-test and post-test to 10 research subjects before and after giving intervention/treatment. The results of the data analysis showed that the level of anxiety to speak before and after the intervention was given had a difference value of 72.1 so that it can be said that Cognitive Behavior Therapy (CBT) has proven effective in reducing the level of anxiety speaking